Fuel and ergogenic aids 2.2 - general (1999)
This third issue of Volume 5 of Coaching Science Abstracts (Volume 5(3): November, 1999 FUEL AND ERGOGENIC AIDS 2.2) reviews 79 articles concerned with substances used to supplement or augment diets with a view to improving performance capacities. At the end of the dietary substances are a few abstracts concerned with ergogenic aids. The issue is divided into the following subtopics; general, carbohydrates (internal effects, dynamics, performance, resistance training), caffeine, other substances (branched-chain amino acids, vitamins, glycerides, high-fat diets, remainder), nasal dilators, and other ergogenic aids.